(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Inguinal hernia repair are very common in day to day general surgical practice. Results of surgical repair are often satisfactory but recurrences following surgery is troublesome both for surgeon and patient. Lichtenstein technique is now the most widely performed technique in groin hernia repair. The aim of this study was to assess short term outcome of inguinal hernia repair by Lichtenstein technique. Methods and materials: In this prospective study, 30 inguinal hernia repairs were performed by Lichtenstein technique between January 2015 and December 2017 in surgery department of Holy Family Red Crescent Medical College Hospital. Patients were scheduled for follow up visits at 1st week, three months and six months in out- patient department. The main outcome measure was early recurrence, groin pain and other complications. Results: In this study age of the patients ranged from 30 years to 78 years, The mean age was 51.93 (±SD 10.12) years. Regarding personal habit, more than half of the patients of inguinal hernia were found to be non-smoker and about 37% of the patients were current smokers. Most of the hernia were of indirect type (18/30) followed by direct type (9/30). In indirect type 55.6% of the hernias were in the right side and the rest were in left side. On an average each operation lasted for 1.18 hours and oral feeding started 12.69 hours after the operation. Two patients (6.7%) had a prolonged recovery and presented with abdominal distention after operation. Postoperative hospital stay that was 2.27 days. 6 (20%) patients developed postoperative urinary retention. Scrotal haematoma formation was observed in 5(17%) cases and local haematoma or seroma formation in incision site was reported in 4 (13%) cases. In 6 patients (20%) we used suction drain tube at tissue plane where mesh was placed for draining of blood or seroma and that drain tube was removed 2nd or 3rd postoperative period. Periincisional skin echymosis, abdominal distension and superficial wound infection, postoperative pyrexia were the other complications reported. No recurrence or mesh rejection or mesh infection were observed within short time postoperative follow up period. Conclusion: Lichtenstein technique is easy to learn, simple to perform and very rationale to perform and recurrence rate is low. Multi-centre studies with larger sample and longer duration of study and more sound study design could bring more insight regarding this issue. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 62-69